Comparison of neonatal outcomes in pregnant women undergoing medication-assisted treatment of opioid use disorder with methadone or buprenorphine/naloxone. (30th December 2022) - Petrich, Michelle; Battin, Megan; Walker, Erin; Brown, Morgan; Abdelwahab, Mahmoud; Ma'ayeh, Marwan; Rood, Kara M.
Abstract: Introduction: The number of pregnant women with opioid use disorder (OUD) has quadrupled from 1999 to 2014. Current first line treatment for OUD in pregnancy is methadone with increasing support for buprenorphine. Limited data exist on use of buprenorphine/naloxone for OUD in pregnancy despite it being standard therapy in the non-pregnant individuals. The aim of this study was to compare neonatal opioid withdrawal syndrome (NOWS) prevalence and characteristics among neonates born to women prescribed methadone and buprenorphine/naloxone. Methods: This is a retrospective cohort analysis of mother–neonate dyads treated with either methadone or buprenorphine/naloxone for OUD in pregnancy who received prenatal care in the substance abuse, treatment, education, and prevention program (STEPP) clinic and delivered at OSU. Primary neonatal outcomes included: neonates diagnosed and treated for NOWS, peak scores on Modified Finnegan Neonatal Abstinence Score (FNAS), number of scores ≥9 on FNAS, and duration of treatment for NOWS. Secondary outcomes included: fetal growth restriction, preterm birth (<37 weeks), neonatal head circumference, birth weight, NICU admission, five-minute Apgar score, and length of hospitalization. Results: From 2013 to 2017, we identified 588 mother–neonate dyads: 149 treated with methadone and 439 treated with buprenorphine/naloxone. Ninety-eight neonates (65.8%) in the methadone group were diagnosed with NOWS requiring pharmacological interventions compared with 170 (38.7%) in the buprenorphine/naloxone group (aOR 3.46, 95% confidence interval (CI) 2.31–5.20, p  < .01). Methadone-exposed neonates were six times more likely to be treated with >1 medication for NOWS (aOR 6.32, 95% CI 2.20–18.13, p  < .01). Fetal growth restriction was diagnosed more often in the methadone group compared to the buprenorphine/naloxone group (aOR 1.73, 95% CI 1.02–2.93, p  < .01). Significant maternal findings were that women using methadone for OUD started PNC earlier (15w vs. 17w, p  = .04) and were less likely to be taking selective serotonin-reuptake inhibitors (SSRIs) (15% vs. 25%, p  = .02) compared to the buprenorphine/naloxone group. Conclusions: Buprenorphine/naloxone treatment for OUD in pregnancy appears safe and has decreased NOWS and pharmacologic intervention for the neonate.